Schizophrenia and Inflammation Research: A Bibliometric Analysis - Sun, He-Li; Bai, Wei; Li, Xiao-Hong; Huang, Huanhuan; Cui, Xi-Ling; Cheung, Teris; Su, Zhao-Hui; Yuan, Zhen; Ng, Chee H.; Xiang, Yu-Tao (Frontiers in Immunology, 2022)
Background: Schizophrenia (SCZ) is a severe psychiatric disorder that involves the role of inflammation. The aim of this study was to explore the field of inflammation-related research in SCZ from a bibliometric perspective. Methods: Regular and review articles on SCZ and inflammation related research were obtained from Web of Science Core Collection (WOSCC) database from its inception to 19 February 2022. R package “bibliometrix” was used to summarize the main findings, count the occurrences of the top keywords, visualize the collaboration network between countries, and generate a Three-Fields Plot. VOSviewer software was applied to conduct both co-authorships and co-occurrence analyses. CiteSpace was used to identify the top references and keywords with the strongest citation burst. Results: A total of 3,596 publications on schizophrenia and inflammation were included. Publications were mainly from USA, China, and Germany. The highest number of publications were found in a list of relevant journals. Apart from “schizophrenia” and “inflammatory”, the terms “bipolar disorder”, “brain” and “meta-analysis” were also the most frequently used keywords. Conclusions: This bibliometric study mapped out a fundamental knowledge structure consisting of countries, institutions, authors, journals, and articles in the research field of SCZ and inflammation over the past 30 years. The results provide a comprehensive perspective for researchers to understand the wider landscape of this research area